Neuromyelitis Optica: An Antibody-Mediated Disorder of the Central Nervous System - Jiwon Oh; Michael Levy (Neurology Research International)
Neuromyelitis optica (NMO) is a recurrent inflammatory disease that preferentially targets the optic nerves and spinal cord leading to blindness and paralysis. The hallmarks of NMO include bilateral optic neuritis and longitudinally extensive transverse myelitis. Woman and African Americans are overrepresented in the US patient population. NMO is associated with the NMO-IgG biomarker, which targets the aquaporin-4 water channel on astrocytes. The humoral pathology of NMO lesions include IgG and IgM deposits and infiltration by granulocytes suggesting that the NMO-IgG may be involved in the pathogenesis of disease. This review of the recent NMO literature covers the clinical features, epidemiology, radiology and pathology of disease and includes discussion of the important basic science research work in the field.